Pelaksanaan Akusisi dalam Rangka Penyelamatan dan Pelestarian Arsip di Dinas Perpustakaan dan Kearsipan Kota Padang - Muliani, Suci; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
AbstractThis article aims to describe the implementation process is the acquisition in order to penyelmatan and preservation of archives in the service of the library and Archives of the city of Padang. This paper writing method that is using descriptive method is done with observation, interview and collect data directly from the original sources namely Department of libraries and Archives of the city of Padang. Based on the discussion can be summed up the steps in the implementation of the acquisition in order to rescue and preservation of archives in the service of the library and Archives city of Padang as follows: first stage second stage archive survey assessment to the third classification Archives Archives implementation of four acquisitions in five archives the archives wrapped doing the stage of indexing and archival storage. the second constraint in the rescue and preservation of Archives first discuss about human resources in both the equipment and the cost of three means the third rescue effort in archival and preservation of the archives of the first two archival facilities and infrastructure equipment the third human resources costs.Keyword: Acquisition,Â Archives.